Printable and recyclable light-assisted enhanced supercapacitor and preparation method thereof
By combining liquid metal with metal oxides through coordination bonds, supercapacitor electrode materials with high conductivity and flexibility characteristics are constructed, which solves the shortcomings of electrode materials in the prior art, realizes the application of light-assisted enhancement and wearable devices, and promotes the reuse of resources.
Patent Information
- Application Number
- CN202510085841.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrode materials of existing supercapacitors have poor conductivity and insufficient rigidity, making it difficult to meet the needs of light-assisted enhancement and wearable devices.
The liquid metal and metal oxides (such as MoO3 and MnO2) are combined through coordination bonds by mechanical grinding to construct printable liquid metal-MoO3 and liquid metal-MnO2 electrode materials to improve conductivity and mechanical properties.
The high conductivity and flexibility characteristics of supercapacitors are achieved, the electrochemical performance enhanced by light assist and support the application of wearable devices, while providing a strategy for recycling liquid metal from supercapacitors, promoting the reuse of resources.
Smart Images

Figure CN119905356A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitors, and in particular relates to a printable and recyclable light-assisted enhanced supercapacitor and a preparation method thereof. Background Art
[0002] With the progress and development of society, emerging industries such as the Internet of Things, wearable bioelectronics, and electronic textiles have put forward new requirements for energy storage devices. As a new type of energy storage device, supercapacitors (MSCs) have the characteristics of ultra-fast charging and discharging, high power density, wide operating temperature, and good cycle stability, and have received widespread attention in the past decade. MSCs usually use metal oxides such as manganese dioxide, cerium oxide, molybdenum trioxide, and vanadium pentoxide as electrode materials to form Faraday MSCs. These materials store energy through redox reactions, making the capacitance value and energy density greater than double-layer MSCs. They can also be used as active materials in photoelectrochemical systems. When these materials are irradiated, photoexcited electrons / holes participate in redox reactions. In addition, photoelectrochemical systems can store photoexcited electrons under illumination. These characteristics indicate that solar energy may affect the energy storage process of supercapacitors. However, the introduction of metal oxides makes the conductivity of electrode materials relatively poor, and its conductivity may be less than one-tenth of that of good conductors, and it is easy to heat up at high current density, resulting in unstable performance of MSCs. At the same time, these electrode materials are rigid and lack the flexibility and mechanical deformation required for wearable devices. Therefore, improving the electrical conductivity and mechanical properties of pseudocapacitive material electrodes is the key to achieving large-scale application of light-assisted MSCs.
[0003] In recent years, liquid metals have been widely studied as an emerging photoresponsive material. Due to the rapid excitation process caused by their free electrons oscillating under light-induced conditions, liquid metal optical materials have attracted great interest in various promising applications. At the same time, liquid metals are one of the most promising candidates for the new generation of soft functional materials and stretchable electronic components. Compared with conductive composite materials, circuits based on liquid metals usually have higher conductivity (3.4×10 6 S m -1 ) and thermal conductivity, flexible stretchability (>1000%) and low toxicity. They are not only mechanically deformable, but also can improve electronic connections and self-healing. However, due to their inherent high surface tension and easy flowability, it is still challenging to directly synthesize liquid metals into leak-free continuous paths or process liquid metals into electrode applications with precise structures. Summary of the invention
[0004] The purpose of the present invention is to provide a printable and recyclable light-assisted enhanced supercapacitor and a preparation method thereof. By utilizing a mechanical grinding strategy, liquid metal and metal oxide are combined through coordination bonds, which can effectively reduce the surface potential energy of gallium indium liquid metal. The constructed liquid metal-MoO3 / / liquid metal-MnO2 supercapacitor shows excellent electrochemical properties.
[0005] To achieve the above object, the present invention provides a method for preparing a printable and recyclable light-assisted enhanced supercapacitor, the method comprising the following steps:
[0006] (1) Gallium and indium are placed in a porcelain boat in a certain proportion, and stirred for 30 to 60 minutes under heating to obtain a uniform liquid metal (liquid metal).
[0007] The mass ratio of gallium-indium alloy in the liquid metal in this step is 75:25, and the heating temperature is 90-120°C.
[0008] (2) The liquid metal obtained in step (1) is transferred to a mortar, and MoO3 is added to the mortar and ground for 30 to 60 minutes until the liquid becomes a slurry, which is called liquid metal-MoO3.
[0009] In this step, the mass ratio of MoO3 to liquid metal is 1:3 to 1:5.
[0010] (3) The liquid metal obtained in step (1) is transferred to a mortar, MnO2 is added to the mortar, and ground for 30 to 60 minutes until the liquid becomes a slurry called liquid metal-MnO2.
[0011] In this step, the mass ratio of MnO2 to liquid metal is 1:5 to 1:7.
[0012] (4) The PET template is processed into an interdigitated microelectrode array template using laser cutting technology.
[0013] The PET template in this step is polyethylene terephthalate, and is etched using a fiber laser with a power of 5W to 20W. The interdigital electrodes are 0.8 cm long, 100 μm to 900 μm wide, and have a gap of 50 μm to 200 μm.
[0014] (5) The slurry obtained in step (2) is transferred to a laser-written PET template, and the template is removed by moving a scraper to obtain a LM-MoO3 interdigitated electrode.
[0015] (6) The slurry obtained in step (3) is transferred to a laser-written PET template, and the template is removed by moving a scraper to obtain a LM-MnO2 interdigitated electrode.
[0016] (7) Polyvinyl pyrrolidone (PVP) and sodium sulfate (Na2SO4) solution are dissolved in deionized water and stirred in an oil bath to obtain a Na2SO4-PVP gel electrolyte.
[0017] The molar mass of polyvinyl pyrrolidone is 2500-24000, the mass is 6 g, the volume of sodium sulfate solution is 12 mL, the concentration is 1 mol / L, the deionized water is 18 mL, the oil bath temperature is 95° C., and the stirring time is 2-3 hours.
[0018] (8) Assembling the LM-MoO3 and LM-MnO2 interdigitated electrodes obtained in steps (5) and (6), dripping the Na2SO4-PVP gel electrolyte described in step (7) into the interdigitated microelectrodes, and encapsulating the interdigitated microelectrodes using a thermoplastic film.
[0019] There is no time sequence restriction among the steps (1), (2), (3) and (4).
[0020] The present invention uses a mechanical grinding method to introduce metal oxides (molybdenum trioxide, manganese dioxide) as solid fillers into liquid metals and combine them under the action of strong shear force. By adjusting the content of metal oxides, liquid metals with high surface tension can be adjusted to liquids with low surface tension, semi-solid pastes, or even solid powders. Coordination bonds are formed between lone electron pairs in metal oxides and empty orbitals of liquid metals. Liquid metal-MoO3 and liquid metal-MnO2 MSC electrodes were prepared by template printing. Liquid metal provides high conductivity and ductility for electrodes. Metal oxides provide pseudocapacitive properties as active materials of electrodes, and at the same time, as solid fillers, adjust the surface tension of liquid metals, so that composite materials can construct precise structural electrodes. The characteristics of the two and the combination to form coordination bonds can improve the electrochemical performance of light-assisted MSCs. In addition, MSC units can be arbitrarily integrated through printing according to different energy and voltage requirements, expanding the application range of next-generation microelectronic devices. At the same time, a strategy for recovering expensive liquid metals from MSCs is formulated to achieve reuse and reduce electronic waste.
[0021] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0022] (1) The present invention uses a mechanical grinding strategy, and the liquid metal and metal oxide are combined through coordination bonds, which can effectively reduce the surface potential energy of gallium indium liquid metal. Liquid metal-MoO3 and liquid metal-MnO2 electrode slurries that can be used for printing are constructed. The photoexcitation characteristics of liquid metal and metal oxide and the combination to form coordination bonds and lattice distortion can improve the electrochemical performance of light-assisted MSCs. The constructed liquid metal-MoO3 / / liquid metal-MnO2 supercapacitors show excellent electrochemical performance. This study provides a new strategy for the preparation of supercapacitors with light-assisted enhanced electrochemical performance.
[0023] (2) The liquid metal-MoO3 and liquid metal-MnO2 materials described in the present invention can be arbitrarily integrated through template printing according to different energy and voltage requirements, thereby expanding the application range of next-generation microelectronic devices.
[0024] (3) The liquid metal-MoO3 and liquid metal-MnO2 materials described in the present invention can recover expensive liquid metal from MSC under specific conditions, thereby achieving reuse and reducing electronic waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the processing process of the liquid metal-MoO3 / / liquid metal-MnO2 micro supercapacitor prepared in Examples 1 to 3.
[0026] Figure 2 Morphological characterization of the liquid metal-MoO3 composite electrode prepared in Example 2: (a, b, c) surface SEM images of LM-MoO3 electrode; (d) SEM image of electrode cross section; (e) EDS image of electrode cross section; (f) HRTEM image and fast Fourier transform of LM-MoO3.
[0027] Figure 3 Electronic pictures showing the flexibility, healing properties and patterning of the liquid metal-MoO3 composite electrode prepared in Example 2.
[0028] Figure 4 The light-enhanced mechanism and performance of the liquid metal-MoO3 / / liquid metal-MnO2 asymmetric micro supercapacitor prepared in Example 2: (a) UV-visible diffuse reflectance spectrum; (b) band gap determined by UV-visible diffuse reflectance spectrum; (c) VB-XPS spectrum of LM-MoO3 and MoO3 electrodes and (d) band structure; (e) schematic diagram of the charge storage mechanism of LM-MoO3 electrode; (f) CV curves of the light-enhanced asymmetric micro supercapacitor under dark and light conditions; (g) comparison of GCD curve and (h) Nyquist plot.
[0029] Figure 5Performance pictures of the liquid metal-MoO3 / / liquid metal-MnO2 asymmetric micro supercapacitor prepared in Example 2: (a) Capacity matching diagram of LM-MnO2 anode and LM-MoO3 cathode; (b) 20-100 mV s -1 CV curves of (c) light-assisted asymmetric micro-supercapacitors at 1.2-2.8 mA cm -2 GCD curves; (d) Capacitance retention of light-assisted asymmetric micro-supercapacitors at different current densities; (e) From 20 mV s -1 To 100mV s -1 Surface capacitance contribution of light-assisted asymmetric micro-supercapacitor; (f) Leakage current curve of light-assisted asymmetric micro-supercapacitor; (g) At 1.6 mA cm -2 (h) Ragone plot comparing the energy and power density of our work with previously reported MSCs.
[0030] Figure 6 Electronic photographs showing the asymmetric wearable applications of liquid metal-MoO3 / / liquid metal-MnO2 prepared in Example 2.
[0031] Figure 7 The recovery mechanism of the liquid metal-MoO3 composite electrode prepared in Example 2, the recovery schematic diagram and the XRD and EDS of the recovered liquid metal. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] In the following embodiments:
[0034] Scanning electron microscope (SEM): Japan REGULUS8100;
[0035] Element Energy Dispersive Spectrometer (EDS): American Apollo XLT SDD;
[0036] Focused ion beam (FIB): FEI Scios 2HiVac, USA;
[0037] Transmission electron microscope (TEM): Japan JEM-2100PLUS;
[0038] X-ray diffractometer (XRD): Japan ULTIMALV;
[0039] X-ray photoelectron spectroscopy (XPS): PHi 5000X, Japan;
[0040] UV-visible spectrum: American PE lambda 750;
[0041] Electrochemical workstation: CHI 660E, Chenhua, Shanghai, China.
[0042] Example 1
[0043] (1) Gallium and indium are placed in a porcelain boat at a mass ratio of 75:25, heated at 90 to 120° C., and stirred for 30 to 60 minutes to obtain a uniform liquid metal (liquid metal).
[0044] (2) The liquid metal obtained in step (1) is transferred to a mortar, and MoO3 is added to the mortar at a mass ratio of 1:5 to the liquid metal, and ground for 30 to 60 minutes until the liquid becomes a slurry, which is called liquid metal-MoO3.
[0045] (3) The liquid metal obtained in step (1) is transferred to a mortar, and MnO2 is added to the mortar at a mass ratio of 1:7 to the liquid metal, and ground for 30 to 60 minutes until the liquid turns into a slurry called liquid metal-MnO2.
[0046] (4) Using laser cutting technology, a 5W to 20W fiber laser is used to etch a polyethylene terephthalate (PET) template to produce an interdigitated microelectrode array template with a length of 0.8 cm, a width of 100 μm to 900 μm, and a gap of 50 μm to 200 μm.
[0047] (5) The slurry obtained in step (2) is transferred to a laser direct writing template, and the template is removed by moving a scraper to obtain a LM-MoO3 interdigitated electrode.
[0048] (6) The slurry obtained in step (3) is transferred to a laser direct writing template, and the template is removed by moving a scraper to obtain a LM-MnO2 interdigitated electrode.
[0049] (7) 6 g of polyvinyl pyrrolidone (PVP) and 12 mL of 1 mol / L sodium sulfate (Na2SO4) solution were dissolved in 18 ml of deionized water and stirred in an oil bath at 95°C for 2 to 3 hours to obtain a Na2SO4-PVP gel electrolyte.
[0050] (8) Assembling the LM-MoO3 and LM-MnO2 interdigitated electrodes obtained in steps (5) and (6), dripping the Na2SO4-PVP gel electrolyte described in step (7) into the interdigitated microelectrodes, and encapsulating the interdigitated microelectrodes using a thermoplastic film.
[0051] Example 2
[0052] (1) Gallium and indium are placed in a porcelain boat at a ratio of 75:25, heated at 90 to 120° C., and stirred for 30 to 60 minutes to obtain a uniform liquid metal (liquid metal).
[0053] (2) The liquid metal obtained in step (1) is transferred to a mortar, and MoO3 is added to the mortar at a mass ratio of 1:4 to the liquid metal, and ground for 30 to 60 minutes until the liquid becomes a slurry, which is called liquid metal-MoO3.
[0054] (3) The liquid metal obtained in step (1) is transferred to a mortar, and MnO2 is added to the mortar at a mass ratio of 1:6 to the liquid metal, and ground for 30 to 60 minutes until the liquid becomes a slurry, which is called liquid metal-MnO2.
[0055] (4) Using laser cutting technology, a 5W to 20W fiber laser is used to etch a polyethylene terephthalate (PET) template to produce an interdigitated microelectrode array template with a length of 0.8 cm, a width of 100 μm to 900 μm, and a gap of 50 μm to 200 μm.
[0056] (5) transferring the slurry obtained in step (2) to a laser direct-written PET template, moving a scraper to remove the template, and obtaining a LM-MoO3 interdigitated electrode;
[0057] (6) transferring the slurry obtained in step (3) to a laser direct-written PET template, moving a scraper to remove the template, and obtaining a LM-MnO2 interdigitated electrode;
[0058] (7) 6 g of polyvinyl pyrrolidone (PVP) and 12 mL of 1 mol / L sodium sulfate (Na2SO4) solution were dissolved in 18 ml of deionized water and stirred in an oil bath at 95°C for 2 to 3 hours to obtain a Na2SO4-PVP gel electrolyte.
[0059] (8) Assembling the LM-MoO3 and LM-MnO2 interdigitated electrodes obtained in steps (5) and (6), dripping the Na2SO4-PVP gel electrolyte described in step (7) into the interdigitated microelectrodes, and encapsulating the interdigitated microelectrodes using a thermoplastic film.
[0060] Example 3
[0061] (1) Gallium and indium are placed in a porcelain boat at a ratio of 75:25, heated at 90 to 120° C., and stirred for 30 to 60 minutes to obtain a uniform liquid metal (liquid metal).
[0062] (2) The liquid metal obtained in step (1) is transferred to a mortar, and MoO3 is added to the mortar at a mass ratio of 1:3 to the liquid metal, and ground for 30 to 60 minutes until the liquid becomes a slurry, which is called liquid metal-MoO3.
[0063] (3) The liquid metal obtained in step (1) is transferred to a mortar, and MnO2 is added to the mortar at a mass ratio of 1:5 to the liquid metal, and ground for 30 to 60 minutes until the liquid turns into a slurry, which is called liquid metal-MnO2.
[0064] (4) Using laser cutting technology, a 5W to 20W fiber laser is used to etch a polyethylene terephthalate (PET) template to produce an interdigitated microelectrode array template with a length of 0.8 cm, a width of 100 μm to 900 μm, and a gap of 50 μm to 200 μm.
[0065] (5) The slurry obtained in step (2) is transferred to a laser-written PET template, and the template is removed by moving a scraper to obtain a LM-MoO3 interdigitated electrode.
[0066] (6) The slurry obtained in step (3) is transferred to a laser-written PET template, and the template is removed by moving a scraper to obtain a LM-MnO2 interdigitated electrode.
[0067] (7) 6 g of polyvinyl pyrrolidone (PVP) and 12 mL of 1 mol / L sodium sulfate (Na2SO4) solution were dissolved in 18 ml of deionized water and stirred in an oil bath at 95°C for 2 to 3 hours to obtain a Na2SO4-PVP gel electrolyte.
[0068] (8) Assembling the LM-MoO3 and LM-MnO2 interdigitated electrodes obtained in steps (5) and (6), dripping the Na2SO4-PVP gel electrolyte described in step (7) into the interdigitated microelectrodes, and encapsulating the interdigitated microelectrodes using a thermoplastic film.
[0069] like Figure 2 As shown, in steps (2) and (3) of Examples 1 to 3, the liquid metal-MoO3 and liquid metal-MnO2 electrode materials are fully ground, and the components are evenly distributed, and the liquid metals respectively wrap MoO3 and MnO2. TEM shows that the insertion of liquid metal leads to the distortion of the MoO3 lattice.
[0070] like Figure 3As shown, in steps (2) and (3) of Examples 1 to 3, the liquid metal-MoO3 and liquid metal-MnO2 electrode materials have good ductility and can be bent without breaking when prepared into thin films by roller rutting. In addition, the liquid metal-MoO3 and liquid metal-MnO2 electrode materials can change the template to achieve electrode patterning. The prepared liquid metal-MoO3 film has good healing properties. The cut liquid metal-MoO3 film can be repaired at high temperature. No signs of healing were observed on the healed liquid metal-MoO3 film. In addition, the repaired liquid metal-MoO3 film can withstand a weight of more than 20 grams.
[0071] In steps (5) and (6) of Examples 1 to 3, the liquid metal-MoO3 and liquid metal-MnO2 interdigitated electrodes assembled into asymmetric microcapacitors have good light-assisted enhancement of electrochemical performance, which is attributed to the fact that under external light stimulation, part of the light directly stimulates the light-responsive material liquid metal to generate photoexcited carriers, and the other part of the light is transferred to MoO3 through the pores in the electrode material to generate photoexcited carriers. Under the synergistic effect of coordination bonds and lattice distortion, E g The photoelectrons pass through the reduced E g Rapidly jump from the valence band to the conduction band, and finally pass through the external circuit. At the same time, the photogenerated holes are transferred to the electrode interface and participate in the electrode reaction. The positively charged photogenerated holes on the electrode surface will attract more negatively charged SO4 in the electrolyte. 2- ions, and the repulsive force between the same ions makes it take longer for the electrode to reach the preset potential. At the same time, after illumination, the positive SO4 2- This provides additional specific capacitance for the composite electrode. The same mechanism also applies to liquid metal-MnO2 electrodes, such as Figure 4 shown.
[0072] The liquid metal-MoO3 and liquid metal-MnO2 interdigitated electrodes described in steps (5) and (6) of Examples 1 to 3 were assembled into asymmetric microcapacitors and the electrochemical performance was tested. Figure 5 (a) Adjust the ratio of LM-MoO3 and LM-MnO2 to achieve the matching of cathode and anode capacities. -1 ), the CV curves of the light-assisted asymmetric microcapacitors are shown even at 100 mV s -1 The scan rate is also close to a rectangle, with no obvious peak, indicating an ideal electrochemical capacitance during the charge and discharge process. Figure 5 (b). The GCD curves at different current densities show a nearly symmetrical shape, indicating that the LM-MoO3 / / LM-MnO2 light-assisted asymmetric microcapacitor has good Coulombic efficiency and reversibility ( Figure 5c), which is consistent with the CV curve. Figure 5 (d) at 1.2 mA cm -2 to 2.8 mA cm -2 The capacitance retention rate of the photo-assisted asymmetric microcapacitor is as high as 81.33% within the current density range. The capacitance contribution of the photo-assisted asymmetric microcapacitor is determined by CV curves obtained at different scan rates. At a scan rate of 100mV s-1, the capacitance contribution reaches 88.25%. The contribution of diffusion decreases with increasing scan rate ( Figure 5 e), indicating that at high scan rates, the pseudocapacitance of TMOs accounts for most of the total capacity, indicating that most of the charge storage in the light-assisted asymmetric microcapacitor is achieved by pseudocapacitance. The leakage current of the light-assisted asymmetric microcapacitor is 1.6 μA, with high stability, see Figure 5 (f). The cycling stability of the photo-assisted asymmetric microcapacitor was recorded using GCD. At 2.4 mA cm -2 After 10,000 charge and discharge cycles at the current density, the capacity retention rate is greater than 90.02%. Figure 5 (g). Figure 5 h Ragone plot comparing the energy and power density of our work with previously reported MSCs, indicating that the asymmetric micro-supercapacitors have good electrochemical performance.
[0073] The liquid metal-MoO3 / / liquid metal-MnO2 prepared in step (8) of Examples 1 to 3 has good practical application value for micro supercapacitors. It can be integrated with wireless charging and used for device energy supply. Figure 6 .
[0074] The liquid metal-MoO3 (liquid metal-MnO2) interdigitated electrodes prepared in steps (5) and (6) of Examples 1 to 3 are placed in a 1M sodium hydroxide (1M hydrochloric acid) solution at room temperature. The liquid metal can be recovered within 5 minutes. The recovered liquid metal consists of Ga and GaIn, with a gallium content of 75.57% and an indium content of 24.43%. The composition of the recovered liquid metal is very close to that of the raw material and has no pollutants. The recovered liquid metal can be reused to make new multifunctional devices to reduce electronic waste. Figure 7 .
[0075] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a printable and recyclable light-assisted enhanced supercapacitor, the method comprising the following steps: (1) Gallium and indium are placed in a porcelain boat in a certain proportion, and stirred for 30 to 60 minutes under heating to obtain a uniform liquid metal LM; (2) transferring the LM obtained in step (1) into a mortar, adding MoO3 into the mortar and grinding for 30 to 60 minutes until the liquid becomes a slurry LM-MoO3; (3) Transfer the LM obtained in step (1) into a mortar, add MnO2 into the mortar and grind for 30 to 60 minutes until the liquid turns into slurry LM-MnO2; (4) Processing the PET film into an interdigitated microelectrode array template using laser cutting technology; (5) transferring the slurry obtained in step (2) to a laser direct-written PET template, moving a scraper to remove the template, and obtaining a LM-MoO3 interdigitated electrode; (6) transferring the slurry obtained in step (3) to a laser direct-written PET template, moving a scraper to remove the template, and obtaining a LM-MnO2 interdigitated electrode; (7) dissolving polyvinyl pyrrolidone and sodium sulfate solution in deionized water and stirring in an oil bath to obtain a Na2SO4-PVP gel electrolyte; (8) Assembling the LM-MoO3 interdigital electrodes and the LM-MnO2 interdigital electrodes obtained in steps (5) and (6), dripping the Na2SO4-PVP gel electrolyte described in step (7) into the interdigital microelectrodes, and encapsulating the interdigital microelectrodes using a thermoplastic film.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of gallium-indium alloy in the liquid metal is 75:25, and the heating temperature is 90-120°C.
3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of MoO3 to liquid metal is 1:(3-5).
4. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of MnO2 to liquid metal is 1:(5-7).
5. The preparation method according to claim 1, characterized in that: In step (4), the PET template is etched using a fiber laser with a power of 5W to 20W.
6. The preparation method according to claim 1, characterized in that: In step (4), the length of the interdigitated electrodes of the template is 0.8 cm, the width is 100 μm to 900 μm, and the gap is 50 μm to 200 μm.
7. The preparation method according to claim 1, characterized in that: In step (7), the molar mass of polyvinyl pyrrolidone is 2500-24000 g / mol, the mass is 6 g, the volume of sodium sulfate solution is 12 mL, the concentration is 1 mol / L, the deionized water is 18 ml, the oil bath temperature is 95° C., and the stirring time is 2-3 hours.
8. A printable and recyclable light-assisted enhanced supercapacitor obtained by the preparation method according to any one of claims 1 to 7.